Production Offshoring and Investment by Japanese Firms - Kang, Joong; Piao, Shi. (Washington, D.C. : International Monetary Fund, 2015)
We trace Japanese corporate investment across different types of firms over the past decades and estimate the main determinants of investment. We find that there are differences in investment behavior between firms expanding abroad and those operating mainly in domestic markets. On the back of a trend increase in production offshoring, investment by large companies, especially those in the transportation sector, is more positively associated with cash flow while responding less to Q ratio. These findings are consistent with the subdued recovery of private investment in recent years despite booming stock markets and the large build up of cash holdings by Japanese corporates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet